Results of a global, patient-based survey assessing the impact of psoriatic arthritis discussed in the context of the Psoriatic Arthritis Impact of Disease (PsAID) questionnaire - Coates, LC; Orbai, A-M; Azevedo, VF; Cappelleri, JC; Steinberg, K; Lippe, R; Lim, I; Eder, L; Richette, P; Weng, MY; Queiro Silva, R; Fallon, L (BioMed Central, 2020)
Background: Psoriatic arthritis (PsA) is a chronic immune-mediated inflammatory musculoskeletal disease, manifesting as peripheral arthritis, enthesitis, dactylitis, spondylitis, and skin and nail psoriasis. A core set of domains for measuring the impact of PsA has been developed, including pain, patient global assessment, physical function, health-related quality of life (HRQoL), and fatigue. To understand the impact of PsA on health domains from a patient’s perspective, a global survey was developed and results reported in the context of the 12-item Psoriatic Arthritis Impact of Disease (PsAID-12) questionnaire.